2019
DOI: 10.7883/yoken.jjid.2018.289
|View full text |Cite
|
Sign up to set email alerts
|

Predominance of ST22-MRSA-IV Clone and Emergence of Clones for Methicillin-Resistant <i>Staphylococcus aureus</i> Clinical Isolates Collected from a Tertiary Teaching Hospital Over a Two-Year Period

Abstract: INTRODUCTION Methicillin-resistant Staphylococcus aureus (MRSA) is an established nosocomial pathogen that causes infections, such as bacteremia, respiratory tract infections, skin and soft tissue infections (SSTIs), bone and joint infections, and urinary tract infections (1, 2). The prevalence rate of hospital-acquired MRSA infections was the highest (>50) in Asia, South America, and Malta, followed by lower prevalence rates (25-50) in Australia, China, Africa, Romania, Greece, Italy, and Portugal (3). The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 29 publications
3
8
0
Order By: Relevance
“…The population of CC22-MRSA isolates increased from 195 isolates in 2016 to 214 in 2018 compared with the 37 isolates that was collected in 2010 ( Udo et al, 2016 ). The observed expansion in the proportion of CC22-MRSA isolates in Kuwait hospitals mimics reports from some Asian and European countries where the numbers of CC22-MRSA isolates are also high ( Marchese et al, 2009 ; Conceição et al, 2013 ; Sunagar et al, 2016 ; Niek et al, 2019 ). Similarly, recent studies in China reported increase in the population of ST22-MRSA isolates among patients suffering from skin and soft tissue infections ( Zhao et al, 2012 ; Xiao et al, 2019 ).…”
Section: Discussionsupporting
confidence: 73%
“…The population of CC22-MRSA isolates increased from 195 isolates in 2016 to 214 in 2018 compared with the 37 isolates that was collected in 2010 ( Udo et al, 2016 ). The observed expansion in the proportion of CC22-MRSA isolates in Kuwait hospitals mimics reports from some Asian and European countries where the numbers of CC22-MRSA isolates are also high ( Marchese et al, 2009 ; Conceição et al, 2013 ; Sunagar et al, 2016 ; Niek et al, 2019 ). Similarly, recent studies in China reported increase in the population of ST22-MRSA isolates among patients suffering from skin and soft tissue infections ( Zhao et al, 2012 ; Xiao et al, 2019 ).…”
Section: Discussionsupporting
confidence: 73%
“…Comparatively, there were fewer second phase surveillance studies of Malaysian MRSA strains (for strains isolated after 2012) [12,29]. Nonetheless, like our findings, two other studies of this phase also noted the higher prevalence of SCCmec type IV compared to other SCCmec types.…”
Section: Discussionsupporting
confidence: 71%
“…Indeed, surveillance on MRSA antibiotic susceptibility is routinely carried out and reported in Malaysia by the Ministry of Health, in conjunction with Malaysia's Malaysian National Surveillance on Antimicrobial Resistance (NSAR) and the country's conformance to WHO's Global Antimicrobial Resistance Surveillance System (GLASS) initiative [10,11]. In addition, a few Malaysian hospitals have also conducted molecular surveillance on local MRSA strains [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The molecular epidemiology of MRSA in bloodstream infections has been described previously, but less frequently in respiratory infections contracted in the ICU [27,28]. CC22 is one of the largest circulating clonal complexes associated with hospital-acquired MRSA in Europe (UK) and Asia (Kuala Lumpur, China) [11,29], while studies of nosocomial pneumonia indicate that CC5 is associated with MRSA strains originating mostly from the US, Europe (Portugal), Asia (China), Africa (Algeria) and Latin America (Argentina and Chile) [18,19,30,31]. Despite the marked heterogeneity of the sequence types in this study, CC22 and CC5 were the main clonal complexes detected.…”
Section: Discussionmentioning
confidence: 95%